DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA SISWA KELAS VI PADA OPERASI HITUNG PERKALIAN DI SEKOLAH DASAR - Mutmainna, St Nurul; Nurjannah, Nurjannah (Jurnal Pendidikan Dasar dan Keguruan, 2023)
This study aims to determine the effect of bullying on the learning motivation of students at SDN 149 Tokinjong. This type of research is an ex-post facto research type with a quantitative approach. The population of this study were students at SDN 149 Tokinjong. The object of this research is the effect of bullying on the motivation of students at SDN 149 Tokinjong. The data collection techniques are observation, questionnaires or questionnaires and documentation. The data analysis technique uses a simple linear analysis technique. Based on the research that has been done and seen the results of research on the effect of bullying on students' learning motivation at SDN 149 Tokinjong, the authors can conclude that bullying has an effect on students' learning motivation. Because based on the data analyzed using SPSS 25, it is known that the tcount value is 13,809 > ttable 1,701, and sig 0.00 < sig 0.05, then Ho is rejected and Ha is accepted. This means that the research conducted by bullying has an influence on the learning motivation of students at SDN 149 Tokinjong. In addition, the R Square number is 0.872 or 87.2%. This shows that 87.2% of students' learning motivation at SDN149 Tokinjong is influenced by bullying behavior and the remaining 12.8% is influenced by other reasons not investigated.